2019
DOI: 10.4000/irpp.325
|View full text |Cite
|
Sign up to set email alerts
|

Open Government in Authoritarian Regimes

Abstract: Open government has long been regarded as a pareto-efficient policy-after all, who could be against such compelling policy objectives as transparency, accountability, citizen engagement and integrity. This paper addresses why an authoritarian state would want to adopt a policy of open government, which may first seem counter-intuitive, and tracks its outworking by examining several facets of the policy in practice. The research uncovers evidence of insidious bureaucratic obstruction and an implementation defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…As one of the interviewees urged, "they tend to hide everything from us (scholars) because they cannot afford to be transparent, even when it comes to non-classified data". These findings are in accordance with findings reported by Kassen,Janenova & Knox,O'Connor,Janenova & Knox and King & Horrocks (3) ) (O'Connor, Janenova, & Knox, 2019 . Similar studies demonstrate that the issue of conducting research in an authoritarian state is quite pervasive.…”
Section: Summary Of the Results And Discussionsupporting
confidence: 93%
“…As one of the interviewees urged, "they tend to hide everything from us (scholars) because they cannot afford to be transparent, even when it comes to non-classified data". These findings are in accordance with findings reported by Kassen,Janenova & Knox,O'Connor,Janenova & Knox and King & Horrocks (3) ) (O'Connor, Janenova, & Knox, 2019 . Similar studies demonstrate that the issue of conducting research in an authoritarian state is quite pervasive.…”
Section: Summary Of the Results And Discussionsupporting
confidence: 93%
“…15 In summary, it can be concluded that public management reforms which were introduced in Turkey in the fi rst two decades of the 21 st century have produced mixed results. It is not plausible to claim that the reform climate continues today in Turkey where public reforms are no longer a priority item on the political agenda (Öniş and Yılmaz, 2009;O'Connor et al, 2019;Bozkurt-Güngen, 2018). Th ere are not any signs that the enthusiasm with reforms continues in central institutions and local governments.…”
Section: Discussionmentioning
confidence: 99%
“…Oleinik et al (2015) have demonstrated the links between the values and perceptions of administrative reform. O'Connor, Janenova and Knox (2019) have demonstrated that administrative reform initiatives in the region have not generated meaningful administrative reform. By using the lens of policy learning to focus on the bureaucrat beliefs that are being updated, we can begin to understand why.…”
Section: Public Administration In Eurasiamentioning
confidence: 99%